Ethnoecology and use of fishes by the Cubeo people from the Cuduyarí River, Colombian Amazonia - Juan David Bogotá-Gregory; Luis Fernando Jaramillo Hurtado; Juan Felipe Guhl Samudio; Edwin Agudelo Córdoba (Journal of Ethnobiology and Ethnomedicine)
Abstract Background Ethnoichthyology studies the knowledge of human communities about the uses, perception, and behavioral characteristics of fish, based on their cosmology, cosmogony, and culture. This study focused on the Cubeo (Pâmiwâ) ethnic group that inhabits the Cuduyarí River (Vaupés, Colombia) provides information on fishing activities, use of fishes, its ecological distributions (occurrence in rivers, pools, and/or streams) and seasonality (occurrence in low and/or high waters). Additionally, names in the Central Tukano language (Cubeo) are provided. Methods The compilation of information was based on a visual catalog prepared from rapid ecological evaluations, previously carried out by the Amazon Institute of Scientific Research SINCHI. Workshops with the indigenous people were held in communities in the lower, middle, and upper sections of the basin to collect information. Network analyses were done to determine the fishing gear selectivity of the most common species and gears used regarding ecosystems. The coherence in the perception of fish resources among the three communities was assessed via multivariate analyses. Results The results showed that a large percentage (89%) of the species are consumed. There is a generalized perception of resource decline, and there is no coherence regarding the ecological and seasonal distributions of fish reported by the three communities. These differences may be due to an effect of the structural characteristics of the basin in the different sectors where the communities are located. Conclusions Species consumed by the Cubeo in the Cuduyarí do not represent a high commercial value at the Amazon River basin scale. Nevertheless, locally, they are the main source of animal protein and most of the time, the sole source of income. The importance of these species must be recognized and must be a priority for conservation. Knowledge related to the fish resource by indigenous groups, including basic information and its usage, is essential to guide and implement management and conservation strategies specific to each region under study.